Strategi Content Marketing dan Online Advertising untuk Meningkatkan Brand Exposure Diraya Gym Jatinangor - Nabila Puti Aisyah; Imam Rafi Adhiyatma (Pusat Riset dan Inovasi Nasional, 2025)
Diraya Gym is a fitness center located in Jatinangor with a large market potential, particularly among university students. However, its social media presence has not yet been optimized to effectively reach and engage the target audience. This project aims to enhance the brand exposure of Diraya Gym through content marketing and online advertising strategies. The study employed a qualitative approach involving interviews, market questionnaires, and social media analysis. Based on the findings, rebranding efforts were conducted, along with the development of content pillars and a content calendar, followed by the implementation of digital advertising campaigns on Instagram and TikTok. The results indicate a significant improvement in brand exposure, with an increase in reach by 80.81%, engagement by 128.71%, and click-through rate (CTR) by 4.46% during the campaign period. Structured and relevant content strategies, combined with the use of digital advertising, proved effective in enhancing brand visibility and interaction. Overall, this project contributes to strengthening the digital marketing foundation of Diraya Gym and serves as a strategic basis for brand development in the digital era.